Trend of antihyperglycaemic therapy and glycaemic control in 184, 864 adults with type 1 or 2 diabetes between 2002 and 2014: Analysis of real-life data from the DPV registry from Germany and Austria. (May 2016) - Bohn, Barbara; Kerner, Wolfgang; Seufert, Jochen; Kempe, Hans-Peter; Jehle, Peter M.; Best, Frank; Füchtenbusch, Martin; Knauerhase, Andreas; Hofer, Martin; Rosenbauer, Joachim; Holl, Reinhard W.; ,
Highlights: In both type 1, and type 2 diabetes, antihyperglycaemic therapy was intensified. The use of insulin analogues strongly increased in all insulin-treated patients. HbA1C increased in type 1, or type 2 diabetes until 2011, but then improved again. Abstract: Aims: To analyse time trends of antihyperglycaemic therapy and glycaemic control in adult subjects with type 1, or type 2 diabetes between 2002 and 2014 in Germany/Austria. Methods: 184, 864 adults with diabetes (35, 144 type 1 diabetes (T1D), 149, 720 type 2 diabetes (T2D)) from the DPV-database documented between 2002 and 2014 were included. Regression models were applied for antihyperglycaemic therapy in T2D (non-pharmacological, OADs only, insulin ± OADs), insulin therapy in T1D (CT, ICT, CSII) and T2D (BOT, SIT, CT, ICT, CSII), for the use of insulin analogues, and for glycaemic control (HbA1C, severe hypoglycaemia), adjusting for confounders sex, age, and diabetes duration. Results: In T1D, CT (2002:19.7%; 2014:16.0%) and ICT (2002:66.8%; 2014:52.4%) decreased, while CSII increased from 13.5% to 31.5%. In T2D, non-pharmacological treatment became less frequent (2002:36.0%, 2014:21.8%), the use of OADs (2002:19.3%, 2014:28.9%) and insulin ± OADs (2002:44.6%, 2014:49.4%) increased. BOT increased from 7.9% to 18.9%, SIT decreased from 12.0% to 8.3%. ICT slightly increased (2002:44.0%, 2014:45.3%), CT decreased (2002:35.8%, 2014:27.2%). Insulin analogues were used more frequently in T1D (rapid-acting:2002:46.8%, 2014:84.8%; long-acting:2002:26.0%, 2014:54.8%) and in T2D (rapid-acting:2002:26.0%, 2014:43.5%; long-acting:2002:13.7%, 2014:53.6%). Until 2011, HbA1C increased in T1D and T2D, but then decreased again. High variability in the rate of hypoglycaemia was observed. Conclusions: This observational study indicates an increased use of insulin pumps in T1D. In T2D, non-pharmacological therapy decreased, and insulin therapy, particular as BOT, rose. An increase in the use of rapid- and long-acting insulin analogues was present in both patient-groups. Time trend was less clear in glycaemic control.